CODE SWITCHING IN EFL CLASSROOM: A NARRATIVE INQUIRY INTO TEACHERS’ EXPERIENCES AND PERCEPTIONS - Maruf, Nirwanto; Asari, Slamet; Nabillah, Indiarti Yasmin (TELL - US JOURNAL, 2023)
This study utilized a narrative inquiry to investigate code switching in EFL teachers’ classroom and their experiences with it. By applying this approach, the study aimed to comprehend the complex nature of code switching in language classrooms through the perspectives of the teachers who utilize it. Ten EFL teachers were selected on the purpose for the study, and data was gathered through semi-structure interviews. The results reveal that EFL teachers varied in their frequency of code switching, with some preferring to use the target language as much as possible, while others employed code switching to enhance student comprehension. Code switching was more prevalent when teaching students with lower language proficiency to facilitate understanding and communication. It was also employed to create a comfortable learning environment, clarify meaning, and address communication breakdowns. However, some teachers were concerned that excessive code switching could hinder students’ language development, and frequent code switching could negatively impact language development. These findings provide valuable perspectives on code switching in EFL classroom, informing language teaching practices and curriculum development. In summary, this study highlights the complex nature of code switching in language classrooms and emphasize the importance of balancing its usage to promote students’ proficiency in the target language.